A protocol for a systematic review on intersectoral interventions to reduce non-communicable disease risk factors in African cities - Ebele R.I. Mogo; Anna Brugulat-Panés; Lisa K. Micklesfield; Charles Ebikeme; Trish Muzenda; Louise Foley; Tolu Oni (Elsevier, 2022)
Objectives: To present the protocol for a systematic review synthesising quantitative and qualitative evidence in academic and grey literature on intersectoral interventions to address non-communicable disease risk factors in urban Africa. Study design: This protocol is developed in accordance with the Preferred Reporting Items for Systematic Review and Meta-analyses Protocols guidelines. Databases to be searched include PubMed, Global Health, SCOPUS, and Web of Science. Grey literature will be sourced from Google, local, regional, and international agencies, colleagues within the GDAR network, international organisations such as the WHO and UN-Habitat, UNICEF's Child Friendly Cities Initiative, Partnership for Healthy Cities, WHO Alliance for Healthy Cities, the African Centre for Cities, as well as grey literature databases such as Greynet and Opengrey. Methods: We will include all quantitative and qualitative study designs that describe any initiatives to address non-communicable disease risk factors through intersectoral interventions, and those that describe associations between such interventions and behavioural health or wellbeing outcomes. We will also include health service interventions that have an intersectoral component and are focused on non-communicable disease prevention. Studies must have been conducted in African countries, published in the past 30 years, and contain primary or secondary data as well as an analysis of these data. Results: We will use the qualitative checklist and the cohort study checklist of the Critical Appraisal Skills Programme (CASP), to appraise the quality of each study included in this review. While the specific framework for data synthesis will be concluded after reviewing the extracted data, we anticipate using a parallel convergent method to synthesise the parallel strands of our study, as it involves analysing the qualitative and quantitative papers separately and then integrating them. Conclusions: This will be the first systematic review to explore intersectoral interventions to address non-communicable disease risk in African cities, thus filling a crucial gap in the literature. The findings of this study will be disseminated across global organisations whose mandates cut across non-communicable diseases prevention, health promotion and healthy urban development. These include but are not limited to the World Health Organization, UN-Habitat, the UN Interagency Task Force on Noncommunicable Diseases Prevention and Control and the NCD Global Coordination Mechanism. We also plan to disseminate our findings to national and provincial stakeholders such as local governments, Ministries of Health and grassroots organisations; intergovernmental organisations such as the African Development Bank, and local and international private foundations such as Dangote Foundation and the Gates Foundation. The pan-African scope of this study makes it eligible to serve as a regional body of work and a resource to inform future interventions, practices, and policies.